Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This originates from the problem $\#3.8$ of Rudin, the problem is as followed:

If $ \sum a_{n} $ converges and if ${b_{n}}$ is monotonic and bounded, prove $\sum a_{n}b_{n}$converges.

I know that if we remove the assumption that $b_{n}$ is monotonic, then the conclusion won't hold. That is, if we have $ \sum a_{n} $ converges and ${b_{n}}$ bounded, we can not reach the conclusion that $\sum a_{n}b_{n}$converges. I think of a counter example as $a_{n}=\frac{(-1)^{n}}{n}$ and $b_{n}=(-1)^{n}$,then $ \sum a_{n} $ converges and ${b_{n}}$ bounded, however, $\sum a_{n}b_{n}$ diverges.

Then my question is, however, I read of a proof the problem without using the assumption that $b_{n}$ is monotonic, and hardly can I find where is wrong in the proof. So can anyone tell my what is wrong in the following proof? Thanks in advance guys!

Exercise $\mathbf{3.8}$

We're told that $\{b_n\}$ is bounded. Let $\alpha$ be the upper bound of $\{|b_n|\}$. We're also told that $\sum a_n$ converges: so for any arbitrarily small $\epsilon$, we can find an integer $N$ such that $$\left|\,\sum_{k=m}^n a_k\right|\le\dfrac{\epsilon}{\alpha}\,\,\text{for all $n,m$ such that $n\ge m\ge N$}$$ which is algebraically equivalent to $$\left|\,\sum_{k=m}^n a_k\alpha\right|\le \epsilon\,\,\text{for all $n,m$ such that $n\ge m\ge N$}$$ which since $|b_k|\le \alpha$ for every $k$, means that $$\left|\,\sum_{k=m}^n a_k b_k\right|\le\left|\,\sum_{k=m}^n a_k \alpha\right|\le\epsilon\,\,\text{for all $n,m$ such that $n\ge m\ge N$}$$ By theorem $3.22$, this is sufficient to prove that $\sum a_n b_n$ converges.

share|improve this question
    
The last inequality is wrong. Just use your example. –  John Dec 6 '13 at 9:06
    
But the OP's counterexample doesn't fit the hypotheses, because $b_n$ is not monotonic. –  TonyK Dec 6 '13 at 9:07
    
Where does the proof use the fact that $b_n$ is monotone? –  Lost Dec 6 '13 at 9:10
1  
@Lost Thanks Lost, my question is that the proof doesnt use the hypothese that $b_{n}$ is monotonic and it seems to give a specious proof, and at first I did not find where is wrong. –  Martin Tien Dec 6 '13 at 9:15

1 Answer 1

up vote 4 down vote accepted

The last inequality is wrong. Just take $n=m+1$ and $a_n = -a_m$. Then $|\sum_{k=m}^na_k \alpha| = 0$, but it certainly doesn't follow that $|\sum_{k=m}^na_kb_k| = 0$ for all possible choices of $b_m, b_n$.

share|improve this answer
    
A bit of correction there - I don't believe this is Rudin's work, but rather someone else's proof that the OP was reading. –  Lost Dec 6 '13 at 9:11
    
The proof isnt Rudin's work, its someone else's work! –  Martin Tien Dec 6 '13 at 9:13
    
OK, thanks. I've edited my answer now. –  TonyK Dec 6 '13 at 9:14
    
@TonyK Thanks, Tony! very helpful! –  Martin Tien Dec 6 '13 at 9:18

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.